TRANSPORT LOGISTICS IN THE ECONOMY OF UZBEKISTAN (Marketing Jurnali, 2024)
Transport is of utmost importance in Uzbekistan. The country's medium-sized territories and high population density, the disunity of industrial and agricultural centres, as well as its remoteness from world markets make having a developed transport system vital for Uzbekistan.